Plant Pyranocoumarins: Description, Biosynthesis, Application - Maria T. Khandy; Anastasia K. Sofronova; Tatiana Y. Gorpenchenko; Nadezhda K. Chirikova (Plants, 2022)
This overview article contains information about pyranocoumarins over the last 55 years. The article is based on the authors’ phytochemical and physiological studies in vivo and in vitro as well as search and analysis of data in literature available on Google Scholar, Web of Science, PubMed, and ScienceDirect before January 2022. Pyranocoumarins are synthesized in plants of the Apiaceae, Rutaceae families, and one species in each of the Cornaceae, Calophyllaceae, and Fabaceae families can synthesize this class of compounds. The physiological role of these compounds in plants is not clear. It has been proven that these substances have a wide range of biological activities: anti-cancer, anti-spasmatic, and anticoagulant, and they also inhibit erythrocyte lysis and accumulation of triacylglycerides. The overview generalizes the modern understanding of the classification, structure, and biological activity of natural pyranocoumarins, and summarizes dispersed data into a unified scheme of biosynthesis. The review analyzes data on the localization and productivity of these substances in individual organs and the whole plant. It discusses a link between the unique structure of these substances and their biological activity, as well as new opportunities for pyranocoumarins in pharmacology. The article evaluates the potential of different plant species as producers of pyranocoumarins and considers the possibilities of cell cultures to obtain the end product.